Heavy caffeine intake in pregnancy and sudden infant death syndrome. Issue 1 (1st January 1998) - Ford, R P K; Schluter, P J; Mitchell, E A; Taylor, B J; Scragg, R; Stewart, A W; ,
Abstract : AIMS: To examine the association between maternal caffeine consumption during pregnancy and the risk of sudden infant death syndrome (SIDS). METHODS: A nationwide case-control study surveying parents of 393 SIDS victims and parents of 1592 control infants. Caffeine consumption in each of the first and third trimesters was estimated by questionnaire. Heavy caffeine intake was defined as 400 mg/day or more (equivalent to four or more cups of coffee per day). RESULTS: Infants whose mothers had heavy caffeine consumption throughout their pregnancy had a significantly increased risk for SIDS (odds ratio 1.65; 95% confidence interval 1.15 to 2.35) after adjusting for likely confounding factors. CONCLUSION: Caffeine intake has been associated with fetal harm and now SIDS. Reducing heavy caffeine intake during pregnancy could be another way to lessen the risk of SIDS. This needs confirmation by others.